Impacto del cambio climático en la producción acuícola de la región Piura, 2005-2019 - Castillo Coveñas, Rebeca Fiorella (2024)
The fisheries sector is a strategic element for Peru's economy, mainly because it is an important source of foreign exchange after mining, so it is particularly important to analyze the impact of climate change on aquaculture production in the Piura region. In this regard, the methodology used consisted of relating the climatic variables of maximum and minimum temperature, precipitation and relative humidity with the production of fan shell, shrimp and tilapia, by applying Hodrick-Prescott filters (lambda = 100) and Dickey-Fuller hypothesis tests. The results show that each production has a different variation of minimum and maximum temperature within the permissible range, so the possibility of making forecasts regarding the effect of climate change is limited by the scarce information available. Climatic variables and their relationship with production explain more than 50% of its behavior, so it can be concluded that shrimp production is stationary in its first level. For the year 2020, the production of fan shells stands out with 36%, above the prawns which had 26%, verifying its stationarity in the second level.